Fabrication and TCAD validation of ambient air-processed ZnO NRs/CH3NH3PbI3/spiro-OMeTAD solar cells - Jarwal D.K.; Kumar A.; Mishra A.K.; Ratan S.; Upadhyay R.K.; Kumar C.; Mukherjee B.; Jit S. (My University, 2025)
This paper reports the fabrication, characterization and simulation of hybrid perovskite solar cells (PSCs) in ambient condition. The proposed PSC structures use a CH3NH3PbI3 hybrid perovskite based active layer sandwiched between a ZnO nanorods (NRs) electron transport layer (ETL) and a spiro-OMeTAD (undoped and doped) hole transport layer (HTL). The ZnO NRs are grown using low-cost solvothermal process at relatively low temperature. The performance of fabricated PSCs are analyzed for both the undoped and doped (with TBP and LiTFSI) spiro-OMeTAD based HTLs. All the solar parameters namely, short circuit current density (JSC), open circuit voltage (VOC), fill factor (FF), power conversion efficiency (PCE) and external quantum efficiency (EQE) are calculated from experimentally measured current density versus voltage (J-V) and wavelength transient characteristics in ambient condition. The maximum PCE of 10.18% is obtained for the doped HTL whereas 9.51% for undoped HTL. The improved performance due to HTL doping is attributed to the enhanced charge transportation of the HTL. The experimental results obtained from the fabricated PSCs are also compared with the SetFos™ TCAD simulation data using drift-diffusion model. The simulated results are observed to be well matched to the experimental data. © 2020 Elsevier Ltd